ZOONOTIC ENDOPARASITES IN CONSUMER FISH COMMERCIALIZED IN THE MARKETS OF IQUITOS CITY, LORETO, PERU - MURRIETA MOREY, Germán Augusto (2022)
The Amazonian ichthyofauna is very important for the commercial development of the Peruvian Amazon, being fish meat the main source of animal protein consumed by the Amazonian population. Despite the high demand for fish in the city's markets, little is known about the parasites present in its meat, and there is a potential risk of acquiring a zoonotic parasite. In this sense, the present study aimed to identify endoparasites in fish sold in markets in the city of Iquitos, reporting the presence of zoonotic parasites in internal organs and the musculature of the fish. Fish samples were acquired from the “Modelo”, “Secada”, “Cardozo” and “Belén” markets, located in Iquitos, Loreto, Peru. In total, 29 species of fish were analyzed, examining the internal organs, cavity and musculature. The results obtained allowed the identification of 15 genera and 22 parasitic species (eight trematodes, four cestodes, two acanthocephalans, 22 nematodes and one pentastomid). The registered zoonotic parasites were: Clinostomum marginatum and Ithyoclinostomum dimorphum (Trematoda), Anisakis sp., Contracaecum sp., Hysterothylacium sp., Terranova sp., Pseudoterranova sp. and Eustrongylides sp. (Nematoda) and Sebekia sp. (Pentastomida). These parasites represent latent risks to the consumer's health if they are accidentally ingested in culinary preparations that use raw or undercooked fish meat as a preparation.